1994
DOI: 10.1083/jcb.124.1.101
|View full text |Cite
|
Sign up to set email alerts
|

A small rab GTPase is distributed in cytoplasmic vesicles in non polarized cells but colocalizes with the tight junction marker ZO-1 in polarized epithelial cells

Abstract: Abstract. Small rab/Yptl/Sec4 GTPase family have been involved in the regulation of membrane traffic along the biosynthetic and endocytic pathways in eucaryotic cells. Polarized epithelial cells have morphologically and functionally distinct apical and basolateral surfaces separated by tight junctions. The establishment and maintenance of these structures require delivery of membrane proteins and lipids to these domains. In this work, we have isolated a cDNA clone from a human intestinal cDNA library encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(111 citation statements)
references
References 88 publications
(84 reference statements)
4
106
0
1
Order By: Relevance
“…This is in agreement with previous studies reporting that in unpolarized cells, such as the ECs shown in Fig. 1 (D-G), Rab13 is present exclusively in cytoplasmic vesicles (33). When placed under a VEGF-A 164 gradient (0 -20 ng/ml) in a Dunn chamber, ECs formed lamellipodia and polarized in the gradient direction (Fig.…”
Section: Syx ϫ/ϫ Ecs Fail To Follow a Vegf-a 165supporting
confidence: 82%
“…This is in agreement with previous studies reporting that in unpolarized cells, such as the ECs shown in Fig. 1 (D-G), Rab13 is present exclusively in cytoplasmic vesicles (33). When placed under a VEGF-A 164 gradient (0 -20 ng/ml) in a Dunn chamber, ECs formed lamellipodia and polarized in the gradient direction (Fig.…”
Section: Syx ϫ/ϫ Ecs Fail To Follow a Vegf-a 165supporting
confidence: 82%
“…Similarly to GFP-Rab13 constructs, we found that VSV-Rab13Q67L localized to the plasma membrane and VSV-Rab13T22N to cytoplasmic structures (supplementary material). Moreover, we also examined the distribution of an other GFP-tagged protein Rab8, which shares high amino acid identity with Rab13 (Zahraoui et al, 1994) and is also associated with tight junctions in MDCK cells (Huber et al, 1993). GFP-Rab8Q67L localized to perinuclear region and to the plasma membrane (supplementary material) was consistent with the localization of endogenous Rab8 in MDCK cells (Huber et al, 1993).…”
Section: Expression Of Gfp-rab13 In Mdck Cellsmentioning
confidence: 86%
“…The transepithelial electrical resistance (TER) can be used to monitor the tightness of the seal between neighboring cells. Because the recruitment of Rab13 to the apicolateral junctional complex occurred at an early stage in the assembly of TJ (Zahraoui et al, 1994;Sheth et al, 2000), we postulated that it might be involved in TJ sealing. Therefore, we measured TER over a 120-h time period of parental MDCK, GFP, GFP-Rab13WT, GFP-Rab13T22N, and GFP-Rab13Q67L cells grown on filters (Figure 2).…”
Section: Expression Of Gfp-rab13q67l Delays the Formation Of Electricmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Sec4p, Rab8 and Rab13 have also been associated with polarized membrane transport. Rab8 has been found to regulate transport from the TGN to the basolateral membrane of polarized MDCK cells (Huber et al, 1993;Ang et al, 2003), and both Rab8 and Rab13 have been associated with junctional complex dynamics in epithelial cells (Zahraoui et al, 1994;Marzesco et al, 2002;Lau and Mruk, 2003;Kohler et al, 2004;Morimoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%